Fabrication and Evaluation of a Portable Biomass Stove for Implementing in Regions without Access to Natural Gas Distribution Network - M. A Ebrahimi-Nik (Ferdowsi University of Mashhad, 2019)
Introduction More than 40 percent of the world population is now dependent on biomass as their main source of energy for cooking. In Iran, the lack of access roads and inefficient transportation structure have made some societies to adopt biomass as the main energy source for cooking. In such societies, inefficient traditional three-wall cook stoves (TCS) are the sole method of cooking with biomass, which corresponds to the large fuel consumption and smoke emission. Biomass gasifier cook stoves have been on the focus of many studies as a solution for such regions. In these stoves, biomass is pyrolized with the supply of primary air. The pyrolysis vapors are then mixed with secondary air in a combustion chamber where a clean flame forms. In this study, a biomass cook stove was manufactured and its performance was evaluated feeding with three kind of biomass wastes (e.g. almond shell, wood chips, and corn cob). Materials and Methods A natural draft semi-gasifier stove was manufactured based on the stove proposed by (Anderson et al., 2007). It had two concentric metal cylinders with two sets of primary and secondary air inlet holes. It had 305 mm height and 200 mm diameter. The stove was fed by wood chips, almond shell, and corn cob. Thermal performance of the stove was evaluated based on the standard for water boiling test. It consisted of three phases of cold start, hot start, and simmering. Time to boil, burning rate, and fire power was measured in minute. A “K” type thermocouple was used to measure the water temperature. Emission of carbon monoxide from the stove was measured in three situations (e.g. open area, kitchen without hood, and kitchen under hood) using CO meter (CO110, Thaiwan).   Results and Discussion Neither particulate matter nor smoke was visually observed during the stove operation except at the final seconds when the stove was going to run out of fuel. The flame color was yellow and partly blue. The average time to boil was 15 min; not significantly longer than that of the LPG stove (13 min). Time to boil in hot phase was almost the same for all fuels which is not in line with the studies reported by (Kshirsagar and Kalamkar, 2014; Ochieng et al., 2013; Parmigiani et al., 2014). This is probably due to the stove body material. In fact, the hot phase test, aims to show the effect of the stove body temperature on the performance. In contrast with the most of the stoves, the one was used in the present study was made of a thin (0.3 mm) iron sheet which has a high heat transfer and low heat capacity. This results in a rapid increase in the stove body temperature up to its highest possible. The longest flaming duration (51 min) was observed by 350 g almond shell. Thermal efficiency on the other hand, was different in using different biomass fuels. The average thermal efficiency of 40.8 was achieved by the stove which is almost three times of open fire. The results from emission test showed that the average of carbon monoxide surrounding the operator in the case of open area, kitchen without hood, kitchen under hood, and traditional open fire were 4.7, 7.5, 5.2, and 430 ppm, respectively. Conclusions The amount of carbon monoxide emitted to the room is in accordance with the US National ambient air quality standards (NAAQS) hence, compared with traditional methods of cooking in deprived regions, the stove burns cleaner with higher efficiency. In order to prohibit respiratory decreases in housekeeping women, this stove could be disseminated in some deprived regions of Iran.